1991
DOI: 10.1002/j.1537-2197.1991.tb15220.x
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Evolution in Dendroseris (Compositae, Lactuceae) From the Juan Fernandez Islands, Chile

Abstract: Leaf flavonoid chemistry was examined from the three subgenera and 11 species of the endemic genus Dendroseris (Compositae, Lactuceae) of the Juan Fernandez Islands, Chile. Eight of the species are restricted to the older island (Masatierra, ca. 4 million years old), which is also closer to the mainland. Three species, one from each subgenus, are restricted to Masafuera, which is younger geologically (1–2 million years old) and 145 km further west of Masatierra. A total of 16 compounds was identified, with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In addition, our current study suggested that D. litoralis is more closely related to D. macrantha than to D. marginata. It has been demonstrated that, based on morphological traits, D. macrantha is most closely related to D. macrophylla on the geologically younger island Masafuera (Alejandro Selkirk), while flavonoid profiles provided no specific insights (Pacheco et al, 1991). The current study strongly suggests a sister relationship between D. litoralis and D. macrantha (100% BS).…”
Section: Phylogenetic Relationships Within Dendroserismentioning
confidence: 48%
See 3 more Smart Citations
“…In addition, our current study suggested that D. litoralis is more closely related to D. macrantha than to D. marginata. It has been demonstrated that, based on morphological traits, D. macrantha is most closely related to D. macrophylla on the geologically younger island Masafuera (Alejandro Selkirk), while flavonoid profiles provided no specific insights (Pacheco et al, 1991). The current study strongly suggests a sister relationship between D. litoralis and D. macrantha (100% BS).…”
Section: Phylogenetic Relationships Within Dendroserismentioning
confidence: 48%
“…Plant materials of seven Dendroseris species were collected previously in the field during four expeditions of the Universidad de Concepción, Chile and the Ohio State University, United States to the Juan Fernández Islands. As acknowleged in the previous studies (Crawford et al, 1987(Crawford et al, , 1992Pacheco et al, 1991), the CONAF (Corporación National Forestal) of Chile issued the permission to collect in the Robinson Crusoe National Park. Our current samples of Dendroseris are representatives of those previous collections.…”
Section: Plant Materials and Dna Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…This latter genus is of interest as it has derived cladogenetically on the older island with three independent dispersals to the younger island and three anagenetic speciations there ( Sanders et al . 1987 ; Pacheco et al . 1991 ; Sang et al .…”
Section: Resultsmentioning
confidence: 99%